PENERAPAN MODEL PEMBELAJARAN CHILDREN LEARNING IN SCIENCE UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA PADA MATERI CAHAYA DAN ALAT OPTIK KELAS VIII SMPN 3 RUMBIO JAYA - Laili, Wirda; Nor, M.; Wakidi, Wakidi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the increase in cognitive learning outcomes of class VIII SMP 3 Rumbio Jaya students by applying the Children Learning In Science learning model to light material and optical devices. The type of research used is true-experiment with the study design was a pretest posttest control group design. The research subjects were class VIII SMP 3 Rumbio Jaya Academic Year 2018/2019 which amounted to 40 students. The research data is the student cognitive learning outcomes test data consisting of pretest scores and posttest scores through the application of the Children Learning In Science learning model. The instrument used to collect data in this study is a written test of cognitive learning outcomes of students with an objective form of light material and optical devices. Data were analyzed descriptively and inferentially. The results of data analysis obtained are there are differences in the increase in learning outcomes between the experimental class and the control class. This is based on the output of the Independent Sample T-Test where the significance value (sig.2 -tailed) is 0.003. Based on the provisions, if (sig.) <0.05 then Ha is accepted. In addition, the results of the student test scores in the experimental class which applied the CLIS learning model also had an average absorptive capacity of 82.06%, and this showed that the absorption capacity of the experimental class was higher than the absorptive capacity of the control class. applying the conventional model of 75,39%. So that it can be concluded that there is an increase in students' cognitive learning outcomes between classes that implement CLIS learning models with classes that apply conventional learning models to light material and optical devices.Key Words: Children Learning In Science, Cognitive Learning Outcomes,Light And Optical Devices.